Prêtres et prêteurs au XIXe siècle - Hudon, Christine (Histoire sociale / Social History, 1993)
Number: 52

Sauvetage archéologique sur le site du chantier naval Munn, BiFj-25, 1993 - Société d'archéomatique Chronogramme-Lauverbec (Société immobilière du patrimoine architectural de Montréal (SIMPA), 1993)
Keywords: Construction navale

Toronto-Ottawa-Montréal: concentrations majeures canadiennes de l'innovation par la recherche-développement - Chevalier, Jacques (The Canadian Geographer / Le Géographe canadien, 1993)
Number: 3

Les contraintes structurelles des finances publiques locales: les budgets municipaux dans la région de Montréal, en 1991 - Collin, Jean-Pierre; Hamel, Pierre J. (Recherches sociographiques, 1993)
issued: 1993-09/1993-12
Keywords: Fiscalité

Taking the Bitter with the Sweet: Sugar Refiners and the Canadian Regulatory State, 1904-20 - Cruikshank, Ken (Canadian Historical Review, 1993)
Number: 3
Keywords: Sucre

L'évolution de l'assurance contre l'incendie au Canada: avant 1804 et de 1804 à 1867 - Parizeau, Gérard (Assurances, 1993)
Keywords: Assurance; Incendies

Montréal portuaire et ferroviaire : actes du 5e congrès de l'Association québécoise pour le patrimoine industriel, Montréal, 8 et 9 mai 1992 - Association québécoise pour le patrimoine industriel (L'Association, 1993)
Keywords: Chemins de fer; Port

Les infirmières de la Métropolitaine au service des Montréalaises - Baillargeon, Denyse (Les Bâtisseuses de la Cité, 1993)
Keywords: Assurance; Femmes; Infirmières

La région de Montréal face au déclin des dépenses militaires - Bélanger, Yves (Cahiers de géographie du Québec, 1993)
Number: 102
Keywords: Armée

Les places et halles de marché au Québec - Bergeron, Yves (Gouvernement du Québec (ministère de la Culture), 1993)
Keywords: Marchés

Les industries manufacturières de haute technologie de la région de Montréal: racines séculaires ou silicon island? - Boisvert, Éric (Université du Québec à Montréal, 1993)

A Study of the Office Rental Buildings in Montreal: Work Paper - Bouchard, Jean (Université Concordia, 1993)
Keywords: Locataires

Hormidas [Hormisdas] Laporte (1850-1934). Une petite maison, un grand homme - Cloutier, Gabrielle (Cahiers d'histoire du Sault-au-Récollet, 1993)
issued: 1993-23-00
Keywords: Alimentation; Assurance; Commerce de détail; Laporte (famille); Magasins; Maires; Épicerie

Le déclin de l'empire montréalais: regard sur l'économie d'une métropole en mutation - Coffey, William; Polèse, Mario (Recherches sociographiques, 1993)
Number: 3
Keywords: Métropole

La fabrication des caractères d’imprimerie à Montréal au milieu du XIXe siècle - Dansereau, Bernard (Revue d'histoire de l'Amérique française, 1993)
Number: 1
Keywords: Imprimerie

Étude historique et analyse patrimoniale des usines Angus - Des Rochers, Jacques (s.n., 1993)
Keywords: Chemins de fer; Usines Angus

Colonial Government Finances in New France, 1700-1750 - Desbarats, Catherine Macleod (Université McGill, 1993)
This thesis considers government finances in New France during the first half of the eighteenth century. By looking directly at government accounts from Canada and l'Ile Royale, and at the administrative structures which gave rise to them, it seeks to reconcile ostensibly rival quantitative and 'administrative' approaches to the literature on France's Ancien regime finances. Evidence is found to suggest that colonial finances emerged as an integral part of French naval finances, not as a result of deliberate policy, but as a by-product of the continued presence of naval troops in the colonies and of the early failure of the Domaine d'Occident to generate net revenue flows to France. Especially in the case of Canada, the accounts of the colonial branch of the naval treasury do not yield a continuous series of figures. Nonetheless, they provide ranges for the size, distribution and changes through time of government expenditure in the colonies, as well as indications of its importance relative to the general level of economic activity, and of the net cost to France of running its North American colonies.

The World of William Notman. The Nineteenth Century Through a Master Lens - Dodds, Gordon; Hall, Roger; Triggs, Stanley (McClelland & Stewart, 1993)
Keywords: Notman; William; Photographie

Pierre-Esprit Radisson - Durand, André (Lidec, 1993)

Le rayonnement géographique du tourisme des congrès à Montréal - Fréchette, Micheline (Université du Québec à Montréal, 1993)
Keywords: Tourisme

Entrevue avec Phyllis Lambert - Gagnon-Pratte, France (Continuité, 1993)
issued: 1993-21-00
Keywords: Centre canadien d'architecture; Lambert; Phyllis

Origines et développement du mouvement ACEF au Québec, 1960- 1970 - Goulet, Henri (Université de Montréal, 1993)

Une approche historique et économique de la société lachinoise, 1667-1767 - Gravel, Denis (Société historique Cavelier-de-LaSalle, 1993)
Keywords: Lachine

Le développement international de Montréal: étude des traits d'internationalité et des perceptions - Lachance, Marc (Université de Montréal, 1993)

Gaz Métropolitain: la force du destin - LeBel, Andrée (Libre Expression, 1993)
Keywords: Électricité

Hydro-Québec et la société québécoise: cinquante ans d'histoire commune - Linteau, Paul-André (Forces, 1993)
issued: 1993-24-00
Keywords: Hydro-Québec; Électricité; Énergie hydraulique

The Evolution of Corporate Debt Issues in Canada from 1970 to 1991 and its Impact on Debt Trusteeships - Lochhead, Louis (Université Concordia, 1993)

Banque royale: au cœur de l'action - McDowall, Duncan (Éditions de l'Homme, 1993)
Translators: _:n3238
Keywords: Banque Royale; Banques

Quick to the Frontier: Canada's Royal Bank - McDowall, Duncan (McClelland & Stewart, 1993)
Keywords: Banque Royale; Banques

L'évolution de l'assurance contre l'incendie au Canada: troisième période: de 1867 à nos jours - Parizeau, Gérard (Assurances, 1993)
Number: 2
Keywords: Assurance; Incendies

Le domaine agricole d'un marchand aux XVIIe et XVIIIe siècles: le Site LeBer à l'île des Sœurs - Pothier, Louise; Duguay, Françoise (Gouvernement du Québec (ministère de la Culture), 1993)
Keywords: Le Ber; Jacques; Marchands; Île-des-Soeurs

Cent ans de transport en commun motorisé - Prévost, Robert (Publications Proteau, 1993)
Keywords: Tramways; Transport en commun

L'empire invisible: histoire des télécommunications au Canada. Volume 1: 1846 à 1956 - Rens, Jean-Guy (Presses de l'Université du Québec, 1993)
Keywords: Bell Canada; Téléphone

L'empire invisible: histoire des télécommunications au Canada. Volume 2: 1956 à nos jours - Rens, Jean-Guy (Presses de l'Université du Québec, 1993)
Keywords: Bell Canada; Téléphone

La compagnie du Saint-Sacrement et la fondation de Montréal - Tallon, Alain (Les origines de Montréal. Actes du colloque organisé par la Société historique de Montréal, 1993)
Keywords: Compagnie du Saint-Sacrement

L'arme favorite de l'épicier indépendant: éléments d'une histoire sociale du crédit (Montréal, 1920-1940) - Taschereau, Sylvie (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 1993)
Number: 1
Keywords: Épicerie

Les petits commerçants de l'alimentation et les milieux populaires montréalais, 1920-1940 - Taschereau, Sylvie (Bulletin du Regroupement des chercheurs-chercheures en histoire des travailleurs et des travailleuses du Québec, 1993)
issued: 1993-24-00
Keywords: Alimentation; Commerce de détail

Les petits commerçants de l'alimentation et les milieux populaires montréalais, 1920-1940 - Taschereau, Sylvie (Université du Québec à Montréal, 1993)
Keywords: Alimentation; Commerce de détail

The Nature of Cooperation between Pharmaceutical Firms in the Greater Montreal Area: A Descriptive Study - Trudeau, Caroline (Université Concordia, 1993)
Keywords: Produits pharmaceutiques

La Banque du Canada: origines et premières années / The Bank of Canada: Origins and Early History - Watts, George S. (Carleton University Press, 1993)